Sustainable workforce development: the role of green HR practice in Malaysian hotels - Helmina Thomas; Stephen Laison Sondoh Jr.; Toh Pei Sung.; Dean Nelson Mojolou (RSIS International, 2025)
Sustainable development emphasizes organizations acting in the interest of current and future stakeholders to ensure long-term survival. This approach has gained importance due to growing concerns over the environment, resources, and social sustainability. The rapid expansion of the hotel industry and the emergence of new hotels have led to intense competition without considering their environmental impact. Dealing with an unpredictable market, changing customer expectations, and business innovation forces them to be equivalent to their competitors. This study seeks to examine the relationship between green HR practices and business sustainability in the hotel industry. Data were collected from 150 sustainable hotels across Malaysia. The study employed SPSS 26.0 and SMART PLS version 3.0 to assess the study’s model. The analysis reveals that green HR practices are partially significant to business sustainability. Practically, the study offers insight for top management and employees to enhance the effectiveness of organizational management functions. Academically, the findings contribute to an evolving body of literature on business sustainability in the hotel industry and provide valuable information for the human resource function. Future research could expand the scope by incorporating other variables.